Etching process of ultrathin metal radiating fin

By pretreatment and electrolytic etching processes on ultra-thin metal heat sinks, the problems of cumbersome etching process and uneven depth in the prior art are solved, and the effects of uniform etching and no perforation are achieved, and the heat dissipation performance of the heat sinks are improved.

CN119615345APending Publication Date: 2025-03-14KEJUNCHENG PRECISION TECH (DONGGUAN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510016104.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The etching process of existing ultra-thin metal heat sinks is cumbersome, and spray etching is difficult to control the etching effect, which may lead to uneven etching depth and perforation of the heat sink.

Method used

The ultra-thin metal heat sink is polished and polished by pretreatment to form a protective film, and then etched with electricity in the electrolyte, and the etching area is closed with mask material and tape to ensure uniformity of the etching depth and no perforation.

Benefits of technology

Through pretreatment and electrolytic etching processes, the surface cleaning and protection of ultra-thin metal heat sinks is achieved, ensuring uniformity of etching depth, avoiding perforation and improving heat dissipation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229969300000091
    Figure BDA0005229969300000091
  • Figure BDA0005229969300000101
    Figure BDA0005229969300000101
  • Figure BDA0005229969300000102
    Figure BDA0005229969300000102
Patent Text Reader

Abstract

The invention relates to an etching process of an ultrathin metal cooling fin, and belongs to the technical field of etching processes. The invention discloses an etching process of an ultrathin metal radiating fin, which specifically comprises the following steps: (1) grinding a millimeter-level metal sheet, then polishing by using a nano aluminum oxide suspension machine, and cleaning by using deionized water; (2) soaking in a protective agent, taking out and airing to obtain the pretreated ultrathin metal radiating fin; (3) a mask material is attached to one face of the pretreated ultrathin metal cooling fin, the other face of the pretreated ultrathin metal cooling fin is completely sealed with an adhesive tape, and then the pretreated ultrathin metal cooling fin is placed in electrolyte; and (4) taking the pretreated ultrathin metal radiating fin as a working electrode, taking an inert material as an auxiliary electrode, and finishing the whole process after electrifying. Through the step of pretreating the ultrathin metal cooling fin, the surface of the cooling fin is cleaned, meanwhile, the protective film formed on the metal surface by the protective agent prevents secondary pollution, the uniformity of the etching depth is ensured in the electrolysis process, and the phenomenon that the cooling fin is perforated is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of etching technology and relates to an etching technology for an ultra-thin metal heat sink. Background Art

[0002] With the development of electronic products, heat dissipation at ultra-thin thickness (less than 1mm) has become a new technical hotspot, and metal heat sinks theoretically still have a very high heat dissipation efficiency at ultra-thin scales. Metal heat sinks, as one of the necessary raw materials in the preparation process of metal heat sinks, can improve the heat dissipation effect by obtaining sufficient vapor space using etching microstructure technology.

[0003] Chinese patent CN114864413A discloses an etching process for an ultra-thin metal heat sink, which process includes the following steps: A. coating a metal sheet with photoresist, and then performing mask exposure and development on the photoresist on the metal sheet; B. spraying an etching liquid on the metal sheet, and etching the position of the metal sheet not covered by the photoresist with the etching liquid to obtain a heat dissipation structure; C. cleaning and degumming the etched metal sheet; D. fixing the metal sheet processed by step C to a grinding disc; E. grinding the metal sheet by a grinder; F. detecting the thickness of the ground metal sheet, and if the difference between the thickness and the set value exceeds a threshold, continuing to perform step E, otherwise performing step G; G. removing the metal sheet from the grinding disc and cleaning it to obtain an ultra-thin metal heat sink. The invention forms an ultra-thin structure by first etching the metal sheet and then grinding it, thereby avoiding the occurrence of etching perforation and deformation. However, the invention process is cumbersome, and the metal sheet is etched by spraying in step B, which cannot control the etching effect and whether the etching depth is uniform. In addition, it cannot guarantee whether the grinding in step D will cause perforation. Therefore, the etching process of the ultra-thin metal heat sink provided by the invention can effectively avoid the above problems. Summary of the invention

[0004] The present invention relates to an etching process for an ultra-thin metal heat sink, and belongs to the technical field of etching processes. The present invention discloses an etching process for an ultra-thin metal heat sink, which specifically includes the following steps: (1) grinding a millimeter-level metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water; (2) then soaking it in a protective agent, taking it out and drying it to obtain a pre-treated ultra-thin metal heat sink; (3) attaching a mask material to one side of the pre-treated ultra-thin metal heat sink, and completely sealing the other side with tape, and then placing it in an electrolyte; (4) using the pre-treated ultra-thin metal heat sink as a working electrode and an inert material as an auxiliary electrode, the entire process is completed after the power is turned on. By performing the pre-treatment step on the ultra-thin metal heat sink, the surface of the heat sink is cleaned, and at the same time, the protective film formed by the protective agent on the metal surface prevents secondary pollution, ensures the uniformity of the etching depth during the electrolysis process, and does not cause perforation of the heat sink.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The etching process of the ultra-thin metal heat sink comprises the following steps:

[0007] (1) grinding a millimeter-scale metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water;

[0008] (2) Then, the pre-treated ultra-thin metal heat sink is obtained by soaking in a protective agent and taking it out and drying it;

[0009] (3) Attach the mask material of the required pattern to one side of the pre-treated ultra-thin metal heat sink, and completely seal the other side and the side with tape, except for the electrode connection, and then put it into the electrolyte;

[0010] (4) The pretreated ultra-thin metal heat sink is used as the working electrode and the inert material is used as the auxiliary electrode. After the power is turned on, the ultra-thin metal heat sink is taken out to complete the entire process.

[0011] Furthermore, in the step (1), the thickness of the millimeter-scale metal sheet is 0.2-0.5 mm, the particle size of the nano-aluminum oxide is 20-50 nm, and the aspect ratio of the metal sheet is 1-1.5:1.2-1.6.

[0012] Furthermore, the method for preparing the protective agent in step (2) comprises the following steps:

[0013] A1: natural plant extract, glycidyl methacrylate, and N,N-dimethylformamide are stirred and heated, and then benzoyl peroxide is added and kept warm. N,N-dimethylformamide is recovered by vacuum distillation on a rotary evaporator to obtain a mixture;

[0014] A2: Mix the mixture with polyaspartic acid in a mass ratio of 1:1 to obtain the protective agent.

[0015] Furthermore, in step A1, the mass ratio of the natural plant extract, glycidyl methacrylate, N,N-dimethylformamide and benzoyl peroxide is 1:2-3:1:0.05, wherein the natural plant extract is pomegranate peel extract, the heating temperature is 120-130°C, the insulation time is 30-40min, and the temperature and pressure of the reduced pressure distillation are 130°C and -0.06~0.08MPa, respectively.

[0016] Furthermore, in the step (3), the mask material is epoxy resin tape, the electrolyte is composed of hydrochloric acid, nitric acid, a chelating agent and distilled water, wherein the mass ratio of hydrochloric acid, nitric acid and chelating agent is 1-2:1:0.5-0.8, and the pH value of the electrolyte is 2-3.

[0017] Furthermore, the chelating agent is one or more of ethylenediaminetetraacetic acid, nitrilotriacetic acid, and diethylenetriaminepentaacetic acid.

[0018] Furthermore, in step (4), the inert material is a graphite sheet or a silver sheet, and its size is 10-12 mm×15 mm.

[0019] Furthermore, in the step (4), the voltage and temperature of the power supply are 8-10V and 30-32°C, the power supply time is 5-10min, and the depth and thickness ratio of the ultra-thin metal heat sink is 0.6:1-0.9:1.

[0020] Beneficial effects of the present invention:

[0021] 1. The present invention performs a pretreatment step on the ultra-thin metal heat sink, so that the surface of the heat sink is cleaned, and the protective film formed by the protective agent on the metal surface prevents secondary pollution, ensures uniform etching depth during the electrolysis process, and does not cause perforation of the heat sink;

[0022] 2. The protective metal sheet made of pomegranate peel extract is soaked to form a protective film on the surface of the pretreated ultra-thin metal heat sink, which has good antioxidant and anti-corrosion effects in the air. When the pretreated ultra-thin metal heat sink is placed in the electrolyte, the hydrochloric acid and nitric acid in the electrolyte have a destructive effect on the protective film. At the same time, the chelating agent and metal ions tend to combine, further enhancing the destructive effect on the protective film, thereby having a buffering effect in the electrolyte to prevent excessive etching from causing penetration of the ultra-thin metal heat sink. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0024] The polyaspartic acid in all the embodiments and comparative examples of the present invention was purchased from Wanhua Tianhe New Materials Co., Ltd., CAS No.: 35608-40-6; the epoxy resin tape was purchased from Chengxing Co., Ltd.; and the tape was purchased from Junqin Co., Ltd.

[0025] Example 1

[0026] The etching process of the ultra-thin metal heat sink comprises the following steps:

[0027] (1) grinding a millimeter-scale metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water;

[0028] (2) Then, the pre-treated ultra-thin metal heat sink is obtained by soaking in a protective agent and taking it out and drying it;

[0029] (3) Attach the mask material of the required pattern to one side of the pre-treated ultra-thin metal heat sink, and completely seal the other side and the side with tape, except for the electrode connection, and then put it into the electrolyte;

[0030] (4) The pretreated ultra-thin metal heat sink is used as the working electrode and the inert material is used as the auxiliary electrode. After the power is turned on, the ultra-thin metal heat sink is taken out to complete the entire process.

[0031] In the step (1), the thickness of the millimeter-scale metal sheet is 0.2 mm, the particle size of the nano-aluminum oxide is 20 nm, and the aspect ratio of the metal sheet is 1:1.2.

[0032] The preparation method of the protective agent in step (2) comprises the following steps:

[0033] A1: natural plant extract, glycidyl methacrylate, and N,N-dimethylformamide are stirred and heated, and then benzoyl peroxide is added and kept warm. N,N-dimethylformamide is recovered by vacuum distillation on a rotary evaporator to obtain a mixture;

[0034] A2: Mix the mixture with polyaspartic acid in a mass ratio of 1:1 to obtain the protective agent.

[0035] In step A1, the mass ratio of the natural plant extract, glycidyl methacrylate, N,N-dimethylformamide and benzoyl peroxide is 1:2:1:0.05, wherein the natural plant extract is pomegranate peel extract, the heating temperature is 120° C., the insulation time is 30 min, and the temperature and pressure of the reduced pressure distillation are 130° C. and -0.06 MPa, respectively.

[0036] In the step (3), the mask material is epoxy resin tape, the electrolyte is composed of hydrochloric acid, nitric acid, a chelating agent and distilled water, wherein the mass ratio of hydrochloric acid, nitric acid and the chelating agent is 1:1:0.5, and the pH value of the electrolyte is 2.

[0037] The chelating agent is ethylenediaminetetraacetic acid.

[0038] In the step (4), the inert material is a graphite sheet having a size of 10 mm×15 mm.

[0039] The voltage and temperature of the power supply in step (4) are 8V and 30°C, the power supply time is 5 minutes, and the depth and thickness ratio of the ultra-thin metal heat sink is 0.6:1.

[0040] The millimeter-scale metal sheet is composed of tin, zinc, aluminum and copper in a mass ratio of 1:1:1:1.

[0041] The pomegranate peel extract was purchased from Snort Biotechnology Co., Ltd.

[0042] Example 2

[0043] The etching process of the ultra-thin metal heat sink comprises the following steps:

[0044] (1) grinding a millimeter-scale metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water;

[0045] (2) Then, the pre-treated ultra-thin metal heat sink is obtained by soaking in a protective agent and taking it out and drying it;

[0046] (3) Attach the mask material of the required pattern to one side of the pre-treated ultra-thin metal heat sink, and completely seal the other side and the side with tape, except for the electrode connection, and then put it into the electrolyte;

[0047] (4) The pretreated ultra-thin metal heat sink is used as the working electrode and the inert material is used as the auxiliary electrode. After the power is turned on, the ultra-thin metal heat sink is taken out to complete the entire process.

[0048] In the step (1), the thickness of the millimeter-scale metal sheet is 0.3 mm, the particle size of the nano-aluminum oxide is 35 nm, and the aspect ratio of the metal sheet is 1.2:1.4.

[0049] The preparation method of the protective agent in step (2) comprises the following steps:

[0050] A1: natural plant extract, glycidyl methacrylate, and N,N-dimethylformamide are stirred and heated, and then benzoyl peroxide is added and kept warm. N,N-dimethylformamide is recovered by vacuum distillation on a rotary evaporator to obtain a mixture;

[0051] A2: Mix the mixture with polyaspartic acid in a mass ratio of 1:1 to obtain the protective agent.

[0052] In step A1, the mass ratio of the natural plant extract, glycidyl methacrylate, N,N-dimethylformamide and benzoyl peroxide is 1:2.5:1:0.05, wherein the natural plant extract is pomegranate peel extract, the heating temperature is 125° C., the insulation time is 35 min, and the temperature and pressure of the reduced pressure distillation are 130° C. and -0.07 MPa, respectively.

[0053] In the step (3), the mask material is epoxy resin tape, the electrolyte is composed of hydrochloric acid, nitric acid, a chelating agent and distilled water, wherein the mass ratio of hydrochloric acid, nitric acid and the chelating agent is 1.5:1:0.7, and the pH value of the electrolyte is 2.5.

[0054] The chelating agent is nitrilotriacetic acid.

[0055] The inert material in step (4) is a silver sheet having a size of 11 mm×15 mm.

[0056] The voltage and temperature of the power supply in step (4) are 9V and 31°C, the power supply time is 7 minutes, and the depth and thickness ratio of the ultra-thin metal heat sink is 0.8:1.

[0057] The millimeter-scale metal sheet is composed of tin, zinc, aluminum and copper in a mass ratio of 1:1:1:1.

[0058] The pomegranate peel extract was purchased from Snort Biotechnology Co., Ltd.

[0059] Example 3

[0060] The etching process of the ultra-thin metal heat sink comprises the following steps:

[0061] (1) grinding a millimeter-scale metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water;

[0062] (2) Then, the pre-treated ultra-thin metal heat sink is obtained by soaking in a protective agent and taking it out and drying it;

[0063] (3) Attach the mask material of the required pattern to one side of the pre-treated ultra-thin metal heat sink, and completely seal the other side and the side with tape, except for the electrode connection, and then put it into the electrolyte;

[0064] (4) The pretreated ultra-thin metal heat sink is used as the working electrode and the inert material is used as the auxiliary electrode. After the power is turned on, the ultra-thin metal heat sink is taken out to complete the entire process.

[0065] In the step (1), the thickness of the millimeter-scale metal sheet is 0.5 mm, the particle size of the nano-aluminum oxide is 50 nm, and the aspect ratio of the metal sheet is 1.5:1.6.

[0066] The preparation method of the protective agent in step (2) comprises the following steps:

[0067] A1: natural plant extract, glycidyl methacrylate, and N,N-dimethylformamide are stirred and heated, and then benzoyl peroxide is added and kept warm. N,N-dimethylformamide is recovered by vacuum distillation on a rotary evaporator to obtain a mixture;

[0068] A2: Mix the mixture with polyaspartic acid in a mass ratio of 1:1 to obtain the protective agent.

[0069] In step A1, the mass ratio of the natural plant extract, glycidyl methacrylate, N,N-dimethylformamide and benzoyl peroxide is 1:3:1:0.05, wherein the natural plant extract is pomegranate peel extract, the heating temperature is 130° C., the insulation time is 40 min, and the temperature and pressure of the reduced pressure distillation are 130° C. and -0.08 MPa, respectively.

[0070] In the step (3), the mask material is epoxy resin tape, the electrolyte is composed of hydrochloric acid, nitric acid, a chelating agent and distilled water, wherein the mass ratio of hydrochloric acid, nitric acid and the chelating agent is 2:1:0.8, and the pH value of the electrolyte is 3.

[0071] The chelating agent is diethylenetriaminepentaacetic acid.

[0072] The inert material in step (4) is a silver sheet having a size of 12 mm×15 mm.

[0073] The voltage and temperature of the power supply in step (4) are 10V and 32°C, the power supply time is 10 minutes, and the depth and thickness ratio of the ultra-thin metal heat sink is 0.9:1.

[0074] The millimeter-scale metal sheet is composed of tin, zinc, aluminum and copper in a mass ratio of 1:1:1:1.

[0075] The pomegranate peel extract was purchased from Snort Biotechnology Co., Ltd.

[0076] Comparative Example 1

[0077] On the basis of Example 2, the etching process of the ultra-thin metal heat sink includes the following steps:

[0078] (1) grinding the millimeter-scale metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water, taking it out and drying it to obtain a pre-treated ultra-thin metal heat sink;

[0079] (2) Attach the mask material of the required pattern to one side of the pre-treated ultra-thin metal heat sink, and completely seal the other side and the side with tape, except for the electrode connection, and then put it into the electrolyte;

[0080] (3) The pretreated ultra-thin metal heat sink is used as the working electrode and the inert material is used as the auxiliary electrode. After the power is turned on, the ultra-thin metal heat sink is taken out to complete the entire process.

[0081] In the step (1), the thickness of the millimeter-scale metal sheet is 0.3 mm, the particle size of the nano-aluminum oxide is 35 nm, and the aspect ratio of the metal sheet is 1.2:1.4.

[0082] In the step (2), the mask material is epoxy resin tape, the electrolyte is composed of hydrochloric acid, nitric acid, a chelating agent and distilled water, wherein the mass ratio of hydrochloric acid, nitric acid and the chelating agent is 1.5:1:0.7, and the pH value of the electrolyte is 2.5.

[0083] The chelating agent is nitrilotriacetic acid.

[0084] The inert material in step (3) is a silver sheet having a size of 11 mm×15 mm.

[0085] The voltage and temperature of the power supply in step (3) are 9V and 31°C, the power supply time is 7 minutes, and the depth and thickness ratio of the ultra-thin metal heat sink is 0.8:1.

[0086] The millimeter-scale metal sheet is composed of tin, zinc, aluminum and copper in a mass ratio of 1:1:1:1.

[0087] The pomegranate peel extract was purchased from Snort Biotechnology Co., Ltd.

[0088] Comparative Example 2

[0089] Compared with Example 2, the difference of Comparative Example 2 is that the pomegranate peel extract in the preparation of the protective agent is replaced with an equal mass of mango extract, and other conditions are consistent with Example 2.

[0090] The mango extract was purchased from Shanyang Lianfeng Biotechnology Co., Ltd.

[0091] Comparative Example 3

[0092] Compared with Example 2, the only difference of Comparative Example 3 is that the pH value of the electrolyte is 1, and the other conditions are consistent with Example 2.

[0093] Comparative Example 4

[0094] Compared with Example 2, the only difference of Comparative Example 4 is that the pH of the electrolyte is 4, and the other conditions are consistent with Example 2.

[0095] 1. Performance Testing

[0096] The ultra-thin metal heat sinks prepared in Examples 1-3 and Comparative Examples 1-4 were used as samples, and an ultra-thin metal heat sink prepared according to an etching process for ultra-thin metal heat sinks provided in Chinese patent CN114864413A was used as a control group. The samples and the control group were observed using a scanning electron microscope to observe whether the etching on the surface of the ultra-thin metal heat sink was uniform and whether it was penetrated;

[0097] Thermal conductivity and heat dissipation uniformity measurement: The ultra-thin metal heat sinks of the sample and control group have a specification of 11mm×15mm. A thermal conductivity tester is used to test the thermal conductivity. At the same time, a micro temperature sensor is used to test ten points at any position of the ultra-thin metal heat sink to determine whether the heat dissipation is uniform.

[0098] Heat dissipation effect test: The ultra-thin metal heat sink of the sample and the control group, with an area of ​​100mm 2 , respectively set on the CPU of the Redmi 3 phone, the smooth side of the heat sink contacts the CPU, the etched side contacts the radiator, keep the phone on, with the brightness at maximum, start the stress test software to make the CPU run at high load, and start the video recording function. Record the temperature data at the 1st, 2nd and 3rd hour.

[0099] The test results are shown in Table 1 and Table 2.

[0100] Table 1 Thermal conductivity and heat dissipation uniformity test results

[0101]

[0102]

[0103] From the analysis of Table 1, it can be seen that the surface depth of the ultra-thin metal heat sink of Examples 1-3 is uniform and there is no penetration phenomenon, while the depth of the comparative example and the control group is different and there is penetration phenomenon. From the thermal conductivity, it can be concluded that the values ​​of the embodiments, comparative examples and the control group are basically the same, which shows that the protective agent will not affect the thermal conductivity of the heat sink. The heat dissipation of the embodiments is uniform, while the heat dissipation of the comparative example and the control group is uneven. Since the embodiment performs a pretreatment step on the ultra-thin metal heat sink, the surface of the heat sink is cleaned, and the protective film formed by the protective agent on the metal surface prevents secondary pollution, and ensures the uniformity of the etching depth during the electrolysis process, and does not cause perforation of the heat sink; in Comparative Example 1, no pretreatment step is adopted, and there is no protective film. The uneven etching and fast etching speed during electrolysis cause a large number of holes to penetrate the heat sink; in Comparative Example 2, mango extract is used instead of pomegranate peel extract, and the obtained protective agent has poor antioxidant effect and the protective agent in the embodiment, so the depth is uneven; in Comparative Examples 3-4, the pH of the electrolyte is greater than or less than the pH range in the embodiment, which affects the depth.

[0104] Table 2 Heat dissipation effect test

[0105]

[0106]

[0107] It can be concluded from Table 1 that the temperature of Example 1 is significantly lower than that of the comparative example and the control group at 1h, 2h, and 3h, and thus the heat dissipation effect of the embodiment is better than that of the comparative example and the control group, among which the heat dissipation effect of Comparative Example 1 is the worst. The uneven depth and penetration phenomenon in Comparative Example 1 greatly affect the heat dissipation effect; the uneven depth in Comparative Example 2 affects the heat dissipation effect; the penetration in Comparative Example 3 affects the heat dissipation effect; and the shallow etching depth in Comparative Example 4 causes poor heat dissipation effect.

[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. The etching process of ultra-thin metal heat sink is characterized by: The etching process of the ultra-thin metal heat sink specifically includes the following steps: (1) grinding a millimeter-scale metal sheet, then polishing it with a nano-alumina suspension machine and washing it with deionized water; (2) Then, the pre-treated ultra-thin metal heat sink is obtained by soaking in a protective agent and taking it out and drying it; (3) Attach the mask material of the required pattern to one side of the pre-treated ultra-thin metal heat sink, and completely seal the other side and the side with tape, except for the electrode connection, and then put it into the electrolyte; (4) The pretreated ultra-thin metal heat sink is used as the working electrode and the inert material is used as the auxiliary electrode. After the power is turned on, the ultra-thin metal heat sink is taken out to complete the entire process.

2. The etching process of the ultra-thin metal heat sink according to claim 1, characterized in that: In the step (1), the thickness of the millimeter-scale metal sheet is 0.2-0.5 mm, the particle size of the nano-aluminum oxide is 20-50 nm, and the aspect ratio of the metal sheet is 1-1.5:1.2-1.

6.

3. The etching process of the ultra-thin metal heat sink according to claim 1, characterized in that: The preparation method of the protective agent in step (2) comprises the following steps: A1: natural plant extract, glycidyl methacrylate, and N,N-dimethylformamide are stirred and heated, and then benzoyl peroxide is added and kept warm. N,N-dimethylformamide is recovered by vacuum distillation on a rotary evaporator to obtain a mixture; A2: Mix the mixture with polyaspartic acid in a mass ratio of 1:1 to obtain the protective agent.

4. The etching process of the ultra-thin metal heat sink according to claim 3, characterized in that: In step A1, the mass ratio of the natural plant extract, glycidyl methacrylate, N,N-dimethylformamide and benzoyl peroxide is 1:2-3:1:0.05, wherein the natural plant extract is pomegranate peel extract, the heating temperature is 120-130°C, the insulation time is 30-40min, and the temperature and pressure of the reduced pressure distillation are 130°C and -0.06-0.08MPa, respectively.

5. The etching process of the ultra-thin metal heat sink according to claim 1, characterized in that: In the step (3), the mask material is epoxy resin tape, the electrolyte is composed of hydrochloric acid, nitric acid, a chelating agent and distilled water, wherein the mass ratio of hydrochloric acid, nitric acid and chelating agent is 1-2:1:0.5-0.8, and the pH value of the electrolyte is 2-3.

6. The etching process of the ultra-thin metal heat sink according to claim 5, characterized in that: The chelating agent is one or more of ethylenediaminetetraacetic acid, nitrilotriacetic acid, and diethylenetriaminepentaacetic acid.

7. The etching process of the ultra-thin metal heat sink according to claim 1, characterized in that: In the step (4), the inert material is a graphite sheet or a silver sheet, and its size is 10-12 mm×15 mm.

8. The etching process of the ultra-thin metal heat sink according to claim 1, characterized in that: The voltage and temperature of the power supply in step (4) are 8-10V and 30-32°C, the power supply time is 5-10min, and the depth and thickness ratio of the ultra-thin metal heat sink is 0.6:1-0.9:1.

Citation Information

Patent Citations

  • Etching process of ultrathin metal radiating fin

    CN114864413A